SYNERGY BETWEEN LOCAL GOVERNMENT AND VILLAGE IN PROMOTING DIGITAL ECONOMY FOR POVERTY ALLEVIATION: A STUDY IN SURABAYA VILLAGE, LIMBANGAN SUBDISTRICT, GARUT REGENCY - Iin Endah Setyawati (Jurnal Dialektika: Jurnal Ilmu Sosial, 2024)
Poverty in rural Indonesia, including Surabaya Village in Balubur Limbangan District, Garut Regency, is a problem that requires innovative solutions. Limited market access, infrastructure and digital literacy are the main obstacles for local MSME players in marketing their products. This research analyzes collaboration between regional governments and village governments in developing the digital economy as an effort to eradicate poverty. Using descriptive qualitative methods, this research collects data through observation, interviews and documentation. The research results show that developing the digital economy through digital literacy training, developing telecommunications infrastructure, and local e-commerce platforms has the potential to increase market access for village MSME products, such as chips and handicrafts. In addition, effective collaboration between local and village governments plays a key role in overcoming obstacles, including lack of digital literacy and limited internet access. Challenges such as lack of synergy between parties and budget constraints still need to be overcome. Through an integrated strategy, digital economic development can empower the people of Surabaya Village, open up wider market opportunities, and reduce dependence on middlemen. This research concludes that government collaboration with a digital economic approach can accelerate poverty alleviation and sustainable development in rural areas.